1984
DOI: 10.1515/cclm.1984.22.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Lagerung und Temperatur auf die Analyse von Steroiden in Plasma und Blut

Abstract: Aus den Untersuchungen folgt, daß Steroide und ihre Plasmabindung in Blut oder Plasma gegenüber den meisten üblichen äußeren Einflüssen relativ stabil sind und auch aus weniger sorgfältig behandelten Proben (Postversänd) in der Regel noch ausreichend zuverlässig analysiert werden können. Influence of storage and temperature on steroid analysis in plasma and blood Summary:In the analysis of steroid Jiormones careful attention is usually paid to blood collection and plasma storage. However, the appropriate care … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…It is unlikely that any thawing occurred before the transport of the serum samples to Uppsala; in any case, steroid hormones are quite stable even when samples are frozen at -20°C and are repeatedly thawed and refrozen (Kley and Rick, 1984;Kley et al, 1985;Sinnecker, 1989).…”
Section: Blood Collectionmentioning
confidence: 99%
“…It is unlikely that any thawing occurred before the transport of the serum samples to Uppsala; in any case, steroid hormones are quite stable even when samples are frozen at -20°C and are repeatedly thawed and refrozen (Kley and Rick, 1984;Kley et al, 1985;Sinnecker, 1989).…”
Section: Blood Collectionmentioning
confidence: 99%
“…As such, this study may have failed to detect changes and correlations that may have been seen if a larger, more representative sample set were evaluated. Finally, although samples utilized in this study had been frozen for approximately 11 yr, and research on long-term stability (years) of plasma samples for hormone and other chemistry analytes is limited, it does appear that corticosteroid and thyroid hormones are relatively tolerant of long-term freezing and freeze-thaw cycles (Kley & Rick 1984, Männistö et al 2007, Lie & Thorstensen 2018; and the observed biochemical data were typical of the species, including previous data for this cohort that were not subject to long-term storage (Innis et al 2009, Keller et al 2012, Stacy & Innis 2015, Hunt et al 2016b, 2019, 2020). The samples used in this study were collected, processed, and stored similarly; thus, even if storage may have affected absolute analyte concen-trations, the relative data are considered comparable among oiling categories and at both time points.…”
Section: Discussionmentioning
confidence: 99%
“…The serum was then transferred to a microtube and frozen at −18 • C. The frozen samples were transported to the laboratory in an icebox. Several studies in the past showed that samples taken and frozen using this technique are very stable, and the concentrations of steroids do not change over time [47,48].…”
Section: Specimen Collection and Pre-laboratory Processingmentioning
confidence: 99%